2014
DOI: 10.1021/es405768n
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Solar Light in Increasing the Toxicity of Silver and Titanium Dioxide Nanoparticles to a Fish Cell Line and Zebrafish Embryos

Abstract: The increasing use of silver (Ag) and titanium dioxide (TiO2) nanoparticles (NPs) in consumer products and their inevitable seepage into the environment prompted us to investigate their potential toxicity to a fish cell line (BF-2) and zebrafish embryos under dark and Simulated Solar Light (SSL) exposure conditions. Using high throughput screening (HTS) platforms, we showed that the oxidative stress-dependent cytotoxicity and embryonic toxicity of NPs were significantly increased upon exposure to SSL. While, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 35 publications
0
46
0
1
Order By: Relevance
“…Other studies that addressed the behavior of AgNPs in natural waters in the presence and absence of humic materials and other organic solutes showed condition-and coating-dependent agglomeration or stabilization of AgNPs (Chappell et al, 2011;Li and Lenhart, 2012;Piccapietra et al, 2012). Moreover, two recent studies reported that AgNPs can be regenerated through sunlightdriven reduction of Ag + by organic matter (Hou et al, 2013;Yu et al, 2014), whereas George et al (2014) reported that solar light increased AgNP dissolution and thus its toxicity to a fish cell line and zebrafish embryos further emphasizing the importance of environmental factors in determining the fate of AgNPs.…”
Section: Environmental Fate Of Agnpsmentioning
confidence: 99%
“…Other studies that addressed the behavior of AgNPs in natural waters in the presence and absence of humic materials and other organic solutes showed condition-and coating-dependent agglomeration or stabilization of AgNPs (Chappell et al, 2011;Li and Lenhart, 2012;Piccapietra et al, 2012). Moreover, two recent studies reported that AgNPs can be regenerated through sunlightdriven reduction of Ag + by organic matter (Hou et al, 2013;Yu et al, 2014), whereas George et al (2014) reported that solar light increased AgNP dissolution and thus its toxicity to a fish cell line and zebrafish embryos further emphasizing the importance of environmental factors in determining the fate of AgNPs.…”
Section: Environmental Fate Of Agnpsmentioning
confidence: 99%
“…0-30 mg/L MWCNTs with 5 mg/L DOM and 10 mg/L MWCNTs with 0-10 mg/L DOM. The last group was to measure the potential contribution of oxidative damage to the algal toxicity of MWCNTs (15 mg/L) as affected by the three DOMs (5 mg/L) in the absence and presence of 0.5 mM N-acetyl cysteine (NAC) (Sigma, USA) which was used as a ROS scavenger [34].…”
Section: 4mentioning
confidence: 99%
“…To evaluate the combined toxicities of mixtures with various combination of UV-filters rather than a single UV-filter, two different types of UV-filters, ethylhexyl methoxycinnamate (EHMC) (UVA protection) (Christen et al, 2011;Kaiser et al, 2012a;Sieratowicz et al, 2011) and Benzophenone-3 (BP-3) (UVB protection) Sieratowicz et al, 2011), were chosen based on their toxicities to aquatic organisms. To better understand the interaction between toxic-and non-toxic substances in a mixture, titanium dioxide nanoparticles (TiO 2 NPs) was also chosen in this study, due to the reports that there was no noticeable toxicity of TiO 2 NPs (George et al, 2014;Marcone et al, 2012;Pavagadhi et al, 2014;Strigul et al, 2009;Zhang et al, 2012;Zhu et al, 2010) to aquatic organisms such as Vibrio fischeri, Daphnia magna, and zebrafish embryo (approximately up to 10 mg/L).…”
Section: Introductionmentioning
confidence: 99%